2021
DOI: 10.3389/fpls.2021.732701
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Tension Enhances the Stability of Nanobubbles in Xylem Sap

Abstract: Air seeded nanobubbles have recently been observed within tree sap under negative pressure. They are stabilized by an as yet unidentified process, although some embolize their vessels in extreme circumstances. Current literature suggests that a varying surface tension helps bubbles survive, but few direct measurements of this quantity have been made. Here, we present calculations of dynamic surface tension for two biologically relevant lipids using molecular dynamics simulations. We find that glycolipid monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…1). Yet, it is unclear how stable these surfactant‐coated nanobubbles are over time, and under which fluctuating conditions (variation in temperature, pressure, gas solubility of xylem sap, gas concentrations in the surrounding xylem tissue) these tiny gas bubbles may expand to form a large embolism (Ingram et al ., 2021; Box Fig. 1).…”
Section: Why Are the Mechanisms Behind Drought‐induced Embolism Forma...mentioning
confidence: 99%
See 2 more Smart Citations
“…1). Yet, it is unclear how stable these surfactant‐coated nanobubbles are over time, and under which fluctuating conditions (variation in temperature, pressure, gas solubility of xylem sap, gas concentrations in the surrounding xylem tissue) these tiny gas bubbles may expand to form a large embolism (Ingram et al ., 2021; Box Fig. 1).…”
Section: Why Are the Mechanisms Behind Drought‐induced Embolism Forma...mentioning
confidence: 99%
“…( 8) Surfactant-coated nanobubbles: tiny gas bubbles can be stable in xylem sap as long as they are coated with surfactants (green) and have a diameter below a critical threshold for a given pressure. The fate of these bubbles, their stability in plant xylem and potential link to embolism are largely unknown (Schenk et al, 2015(Schenk et al, , 2017Ingram et al, 2021). ( 9) Wettability of the inner conduit wall: inner conduit walls must be hydrophilic for an optimal solid-liquid interface (contact angle between water and conduit wall < 90°), while hydrophobic walls (contact angle > 90°) attract surface nanobubbles that may trigger embolism (Zwieniecki & Holbrook, 2000;McCully et al, 2014;Schenk et al, 2017;Brodersen et al, 2018New Phytologist (2022…”
Section: What Is Known About Drought-induced Embolism Formation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this applies to all the drivers of embolism formation depending on gas dynamics discussed above. If embolism formation, for instance, was driven predominantly by the expansion of nanobubbles that exceed a critical size (Schenk et al ., 2017; Park et al ., 2019; Ingram et al ., 2021), a single bubble exceeding this threshold size would be sufficient to cause the complete loss of functionality of the corresponding vessel. Similarly, if emboli spread predominantly via gas diffusion through pit membranes (Guan et al ., 2021), it would only take one large enough bubble coming out of solution, for example after a temperature increase (see fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found no effect of dissolved gas on bubble nucleation above À10 MPa (Hemmingsen, 1977(Hemmingsen, , 2006, but that research did not account for conditions existing in xylem; (2) nanobubbles present in sap may rapidly expand, depending on the pressure and gas concentration. This process would likely depend on the nature of the surfactant layer, such as the composition of polar lipids (Ingram et al, 2021). Regardless of the mechanism of embolism initiation, the fact that embolism propagation can temporarily degas the sap in the surrounding vessels and xylem tissue would delay initiation of further embolisms until the gas concentration locally reaches a certain threshold again.…”
Section: Introductionmentioning
confidence: 99%